The Adaptation of Educational Institutions in Managing Intellectual Property for Online Learning - ไตรแสงรุจิระ ณัชนันทน์; Kanchai, Pattamon (Journal of MCU Phetchaburi Review, 2026)
This article examines the challenges facing copyright law in the era of online education. It compares three key legal frameworks: Fair Use (USA), Fair Dealing (UK), and the Two-Step Test (Thailand). The goal is to find a balance between protecting the rights of creators and promoting access to knowledge in the digital world. The American Fair Use system is notable for its flexibility. It uses a "Four-Factor Test" that allows courts to interpret the law based on new technologies. In contrast, the British Fair Dealing system relies on a specific list of exceptions (Enumerated Exceptions). While this provides clear rules for teachers and students, it may lack the flexibility needed for new educational innovations. In Thailand, Section 32 of the Copyright Act is based on the Two-Step Test. This means that using copyrighted work is allowed only if it does not interfere with the owner’s normal profits and does not unfairly harm the owner’s legal rights. However, the COVID-19 pandemic revealed that these existing rules might not be enough for international online learning. Issues such as recording live online classes or accessing digital libraries remain legally unclear. The comparative study suggests that Thai law needs to be updated to meet international standards, especially by creating clearer exceptions for the "digital environment." The analysis concludes that a successful balance in modern education depends not on strict penalties, but on the law’s ability to adapt to technology. This ensures that digital resources are accessible and fair without discouraging creators from producing new works.